on March 10 at 06:05PM
I got this problem from Card Review section...
C: not B==>C
Ok, I see that after I wrote out the question I have "not B" from conclusion in common the "not B" contrapositive of P1.
I wrote it out like this: not B==>not A==>C then I wrote it in what I believe to be the contrapositive: not C==>A==>B
I made the assumption that the answer was "not C==>A based upon the previous question which was the same thing (see below)
C: not A==>B
again you have in common the "not A" from conclusion with the contrapositive of P1. I wrote out as such: not A==>not X==>B then I assumed the correct procedure was to rewrite it in reverse as such:
The correct answer with the problem was "not B==>X"
The correct answer in the first question is "not A==>C, I assumed incorrectly. What am I doing wrong?
on March 10 at 06:13PM